Academic Perfectionism of High-Ability and High-Achieving Students in Mathematics and Science: Differential Relations by Identification Criteria of Giftedness. Issue 3 (3rd July 2021) - Yi, Soohyun; Gentry, Marcia
ABSTRACT: We investigated whether gifted students' academic perfectionism is associated with their intellectual abilities or learned behaviors as they aim for achievement. Comparing four groups classified by achievement and intellectual ability among 443 Korean students, we examined the differential relations between gifted students and academic perfectionism by identification methods of giftedness. Using multigroup confirmatory factor analysis and multiple indicators multiple causes analysis, we found that students identified by their high intellectual ability were neither positive nor negative perfectionists. For high-achieving students, appropriate uses of perfectionistic self-regulation in academic settings were beneficial for their achievement. However, those students had a higher risk of depression when they lost control over their academic plans and behaviors, overwhelmed by their perfectionistic beliefs and excessive self-evaluations. The findings can be applied to the guidance and counseling for gifted students and underachieving students.